The family with two front doors - Ciddor, Anna (Minneapolis, MN : Kar-Ben Publishing, 2018)
The days and nights of the Rabinovitch family--a rabbi, his wife, and their nine children who live in the Jewish quarter of Lublin, Poland, in the 1920s--are filled with joy, adventure, and ritual, but the biggest adventure occurs one summer when the oldest daughter Adina is betrothed to a young man from Warsaw. Based on the history of the author's Nana Nomi.
The letter -- The market -- Beggar's Day -- Gefilte fish -- Mama's wig -- Braiding the Challah -- Chaim's disaster -- Is it too late? -- The Sabbath queen -- The strangers -- Shabbos -- Nightfall -- It's today -- Inspection of the bride -- The dowry -- The betrothal -- The picnic -- Preparations -- The haircut -- Mordechai arrives -- The chuppah -- Celebrations -- The last dance -- Author's note -- Glossary.
Originally published in 2016 by Allen & Unwin.
Ages 8-12.
Ages 8-12.
Keywords: Rabinovitch, Nomi -- Family -- Juvenile fiction; Rabinovitch, Nomi -- Family -- Fiction; Jews -- Poland -- Juvenile fiction; Families -- Poland -- Juvenile fiction; Arranged marriage -- Juvenile fiction; Poland -- History -- 1918-1945 -- Juvenile fiction; Poland -- Social life and customs -- Juvenile fiction; Jews -- Poland -- Fiction; Family life -- Poland -- Fiction; Arranged marriage -- Fiction; 1918-1945; Fiction; Historical fiction; History; Juvenile works; Historical fiction; Historical fiction